2021
DOI: 10.31235/osf.io/xykdg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

School Segregation and Native Flight. Evidence from School Catchment Area Borders.

Abstract: Ethnic or racial segregation in schools and neighborhoods remains a persistent reality in most major cities in Western countries. Although extensively theorized, determining the exact mechanisms that produce such patterns has proven difficult. In this article, we investigate one of the potential causes of ethnic segregation in schools; native flight motivated by parents’ school preferences. Both observational and experimental evidence suggests that native or White parents have a strong preference for racially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Another related explanation is that some parents may hold preferences for schools with a low concentration of ethnic minority pupils (Nielsen and Andersen, 2019), such that native parents of young children move selectively to avoid schools with high minority concentrations. Wessel and Nordvik (2019) suggested that this may be the case in Norway, and other recent studies support this notion (Bjerre- Nielsen and Gandil, 2020;Kauppinen et al, 2020;Rogne et al, 2021). Our analysis of parents and nonparents also clearly supports such an argument.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Another related explanation is that some parents may hold preferences for schools with a low concentration of ethnic minority pupils (Nielsen and Andersen, 2019), such that native parents of young children move selectively to avoid schools with high minority concentrations. Wessel and Nordvik (2019) suggested that this may be the case in Norway, and other recent studies support this notion (Bjerre- Nielsen and Gandil, 2020;Kauppinen et al, 2020;Rogne et al, 2021). Our analysis of parents and nonparents also clearly supports such an argument.…”
Section: Discussionsupporting
confidence: 85%
“…A recent study from Denmark (Bjerre- Nielsen and Gandil, 2020) has shown that many parents respond to the socioeconomic and ethnic composition of their local school, and the redrawing of attendance boundaries, either by relocating or by enrolling their child in a private or a different public school. Similar studies from Norway (Rogne et al, 2021) and Finland (Kauppinen et al, 2020) have also shown that schools are an important factor in parents' moving decisions.…”
Section: Out-migration Flight and Avoidance In Europementioning
confidence: 56%
“…As enrollment to upper secondary school is based on GPA and not local catchment areas, the role of neigborhood segregation is not discussed here but is addressed for instance by Bernelius and Vilkama (2019), by Boterman (2019), and by Oberti and Savina (2019). See also Rogne et al (2021) for a study on the causal relationship between school-and neighborhood segregation in Norway. 3.…”
Section: Fundingmentioning
confidence: 99%